Aspect‐Oriented Architecting Using Architecture Frameworks. Issue 1 (20th September 2021) - Martin, James N.
Abstract: In the early days of systems engineering, we had a few tried and true methods for depicting the structure and behavior of a system, such as functional flow diagrams, control flow diagrams, state transition diagrams, schematic block diagrams, and system breakdown structure. Nowadays we have a wider variety of choices when it comes to the creation of architecture views. The Unified Architecture Framework, for example, defines 71 possible architecture views that can be created. An easy and intuitive way to navigate the many available offerings was needed. Hence, most architecture frameworks have adopted a "grid" approach to help organize the various views. One of the key dimensions of this organizing approach is the use of architecture aspects. This paper will examine the various frameworks to determine how they organize their views and how they address the different aspects and perspectives of the architecture being described. These concepts were used as the basis for an aspect‐oriented architecting approach reflected in the recently revised version of the ISO 42010 standard on architecture description.